Peran Kepemimpinan Kepala Sekolah dalam Mendorong Profesionalisme Guru Sekolah Dasar - Hasbi, Hasbi (Universitas Nusa Cendana, 2025)
Principal leadership is an important factor in encouraging the creation of teacher professionalism in elementary schools. Principals who have a transformative, participatory, and visionary leadership style are able to create a school culture that supports the continuous development of teacher professionalism. This study aims to examine in depth the role of principal leadership in improving elementary school teacher professionalism through a literature study approach from various current academic sources. Teacher professionalism is not only seen from the aspects of pedagogical, professional, social, and personality competencies, but also from attitudes towards lifelong learning, involvement in curriculum development, and adaptation to changes in 21st century education. The results of the study show that effective leadership can encourage teachers to innovate, collaborate, and increase their professional commitment and responsibility. Principals also play a role in providing training, conducting constructive supervision, and creating a positive and supportive work environment. These findings confirm that principals are not only administrative managers, but also strategic learning leaders. Therefore, strengthening the leadership capacity of principals is crucial to encourage educational transformation at the elementary school level. This study recommends the importance of leadership training programs that focus on teacher professionalism development as part of improving the quality of education.